Analyzing the Dominant Role of Philosophy in Education: A Systematic Literature Review on Curriculum and Pedagogical Innovations - Ahzan, Sukainil; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (Reflection Journal, 2024)
Educational philosophy plays a dominant role in shaping educational theory and practice by providing an epistemic and ethical foundation. This study examines recent literature (2023-2024) to analyze how philosophical concepts, such as Kuhn’s paradigm shifts and culturally rooted approaches like Ubuntu and Ujamaa, influence curriculum design and teaching methods. Using the PRISMA systematic review method, this research identifies 35 relevant documents and conducts an in-depth analysis of 13 journal articles discussing the role of philosophy in education. The findings indicate that philosophy contributes to enhancing critical literacy, epistemic decolonization, and strengthening inclusive educational strategies. This study also highlights the challenges in applying philosophical principles in global education systems, which are still predominantly influenced by Western-based curricula. Through a comprehensive literature review, this research asserts that educational philosophy is not only of academic value but also has practical implications for improving the relevance and quality of education. Therefore, integrating philosophical thought into education can serve as an innovative solution for creating a more inclusive, reflective, and contextual learning system.